Effects of Walnut Bark Extract on the Human Platelet Aggregation, Adhesion, and Plasmatic Coagulation In Vitro. (3rd January 2023) - Amirou, Asmae; Razzok, El Mahdi; Legssyer, Abdelkhaleq; Ziyyat, Abderrahim; Aziz, Mohammed; Bnouham, Mohamed; Zaid, Younes; Berrabah, Mohamed; Mekhfi, Hassane
Abstract : Thrombosis is the formation of a clot within a blood vessel. Antithrombotic drugs are used for treating thrombosis, which can be the cause of hemorrhage. Currently, there is a need to discover novel antithrombotic drugs. Walnut is widely used to treat a wide range of health complaints. In this study, walnut bark extract was tested in hemostasis parameters: platelets adhesion, aggregation, and plasmatic coagulation in human blood. The crude aqueous extract of walnut bark was prepared by infusion and tested in vitro on hemostasis. Through blood collection from healthy volunteer donors, we studied different parameters of the primary hemostasis: platelet adhesion on the collagen-coated surface under flow, ADP, collagen, thrombin, and arachidonic acid-induced platelet aggregation, and of the secondary hemostasis by measuring prothrombin time (PT) and activated partial thromboplastin (APTT) parameters. All experiments are realized in the absence and presence of the extract and repeated at least twice. The obtained data showed that the extract (1 and 2 mg/mL) significantly (p < 0.001 ) reduced the activated platelet adhesion on the collagen-coated surface. In the same way, the effect of the extract on platelet aggregation seems to depend on its concentration and on the nature of the agonist. The strongest inhibition of aggregation was observed in the case of collagen at 1 mg/mL, while there was no observed effect on arachidonic acid-induced aggregation. Moreover, the extract (1 mg/mL) affects the extrinsic, intrinsic, and common pathways of the human blood coagulation cascade by extending significantly (p < 0.001 ), both PT and APTT times. This study provides evidence that walnut bark extract, by its antiadhesive, antiaggregant, and anticoagulant activities, could be considered as a serious source of biological compounds for the prevention and treatment of thrombosis.